Correlation and Path Coefficient Analyses in Sugarcane (Nepal Agriculture Research Journal, 2010)
This study was conducted to determine the contribution of different traits to cane yield insugarcane (Saccharum officinarum L). Sixty-five clones were evaluated in a replicated fieldexperiment at Sugarcane Research Programme, Jitpur, Nepal in 2003 for six morphologicalcharacters under irrigated conditions. Analysis of variance revealed significant differences for allthe characters studied. Cane yield showed positively and highly significant correlation withsingle cane weight, stalk length and millable cane number. There was also positively significantcorrelation of cane diameter and number of internode with cane yield. Length of internode hadpositive non-significant correlation with cane yield. Single cane weight had the highest positivedirect effect on cane yield followed by millable cane number. Stalk diameter and stalk lengthwas positively and significantly correlated with cane yield, which was due to indirect effect ofsingle cane weight. Results indicate that the genotypes should be selected on the basis of singlecane weight and millable cane number for getting higher sugarcane yield.Key words: Cane yield; correlation; path coefficient; sugarcaneDOI: 10.3126/narj.v6i0.3340Nepal Agriculture Research Journal Vol.6 2005 pp24-27